The importance of computer-aided courses in architectural education - Guney, D. (ELSEVIER SCIENCE BV, 2015)
Intensive technology usage in education has been increasing in every field recently. Because computer based visual technology has been developing and becoming the most popular trend in the recent years. In addition to these decreasing prices of the computer based systems make this trend more attractive. Architectural education is one of the most difficult and expensive education and based on visual material. That's why computers and complicated software usage in architectural education has increased dramatically. Using these software, an architecture student can perform his/her project design spending less energy-time but more realistic. But the disadvantage of these systems is to make students computer addicted and design their project without creativity. This paper aims to study advantages and disadvantages of this trend and to find a balance level. According to this concept, courses in architectural design are investigated. What kind of computer systems and software use in education is searched? Based on response of students, the advantages and disadvantages of this trend are studied. (C) 2015 Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
Keywords: DESIGN; CAD; Education & Educational Research; Social Sciences - Other Topics